نظرية الشريعة الإسلامية في الحقوق و الواجبات الزوجية - Wahyu Fitrianoor; Anisah Norlaila Hayati; Nor Fadillah (MAQASHIDUNA: Jurnal Hukum Keluarga Islam, 2025)
The Prophets sent by Allah SWT to realize human potential itself. In their role the Prophets and Apostles brought teachings called Sharia, the contents of which were in the form of efficient and concessional rules for mankind. These mature regulations must contain obligations and rights that must be carried out and fulfilled. This paper aims to reveal the position of human rights and obligations in the perspective of Islamic philosophy, including ontology studies, in the form of: Ontology covers, what is the meaning of Islamic law, rights, and obligations? Epistemology includes about, how are rights and obligations equal, what are rights as a consequence of carrying out obligations, what are the rights of God and the rights of servants, and does God have obligations? Axiology includes: paying for rights immediately, and having Islamic character. There are three findings in this discussion, namely: 1) Islamic law is an absolute idea from Allah SWT as the Creator of the Universe, which was given through revelation to his messenger, which is complex, universal, systematic, and continuous. 2) obligations are demands that have an impact on rights, a balance between the two is a necessity according to Islamic law, where this balance will create harmony and peace for mankind itself. 3) God Almighty, and Willing, does not depend on any absolute power, so that this obligation or right does not detract from his majesty, and balancing the two is purely for the benefit of mankind itself, both in life in this world and in the hereafter. Keywords: Rights & Obligations, Islamic Philosophy, Islamic Law.